Beef Cattle Farmers’ Group Cohesion in Bantul and Sleman Regencies Yogyakarta Special Region, Indonesia - Fransiskus Trisakti Haryadi; Rini Widiati; Tri Anggraeni Kusumastuti; Siti Andarwati (Journal of Agricultural Extension, 2019)
The study analyze the cohesion level of beef cattle farmers’ groups of Bismo in Bantul and Sido Makmur in Sleman Regencies Yogyakarta Special Region. All the active members of the groups were selected as respondents. The descriptive analysis was based on the components forming group cohesion including farmers’ attractiveness to groups’ goals, group activities, membership of the group, and interpersonal relationship among the members of the group. The results show that there was a difference in the kind of components in forming group cohesion between Bismo and Sido Makmur Groups. Bismo group had group activities as main attraction (95.98%) for its members to commit to the group, while the membership of the group was the main indicator of attraction (97.33%) for the member of Sido Makmur to stay in a group. Although the indicator of attractions was cohesion including interpersonal and farmers’ group goal were in high score achievement percentage for both of the Groups of Bismo (89,81% and 88.21%) and Sido Makmur (88.98% and 86.67%), but they had not been used optimally yet as the main reference by the farmers to commit to the groups. The study concluded that there was a high category level of beef cattle farmers’ group cohesion for both Bismo and Sido Makmur groups. The farmers’ group activities and membership of the group were the main indicators of attractions of beef cattle farmers’ group cohesion. The government through their field extension workers should always improve beef cattle farmers’ attitude towards the group goals.